Systematic Review of Misconceptions in Kinematics: Identification, Causes, and Remediation - Uci Rahmadani; Putri Dwi Sundari; Hidayati Hidayati; Wahyuni Satria Dewi (Postgraduate, University of Mataram, 2023)
The purpose of this study was to find out the topics that become students' misconceptions in kinematics, the causes that can trigger misconceptions, and the remediation used to overcome these misconceptions. The method used in this research was the systematic review method. Based on the data analysis, it was found that the biggest misconception among students was in straight motion. Several causes trigger the emergence of misconceptions in kinematics, where the causes that often arise come from the students themselves, namely, students' preconceptions or initial conceptions, students' abilities, students' cognitive development stages, wrong intuitions, and students' reasoning.Â The remediation that was often used to remediate misconceptions was the use of learning models, for instance, generative models.